Ecological succession in oligotrophic pastures of central Spain - Pineda, F D; Nicolas, J P; Rou, A; Galiano, E F (Plant Ecology, 1981)
The dynamics of oligotrophic pastures were analyzed in the area of El Pardo (Central Spain), and related with geomorphological features and time elapsed since the last ploughing. A sampling of the area was carried out regarding these two factors. The data were subjected to correspondence analysis, which showed the progressive replacement of species related to succession, variation along slopes, with a tight interaction between both phenomena. The correspondence between vegetation change and slope geomorphology is closer as succession progresses.
Keywords: Central Spain; correspondence analysis; geomorphology; grassland; slope; succession